Anarchism and childhood: anarchist literature for children - Gallo, Sílvio (2021)
This article discusses the production of literature by anarchist collectives and publishers, focusing on children’s books. It invests in a discussion methodology of three children's books produced by anarchists, namely: A Cura (Brazil, 2015), A Rule is to Break (United States, 2012) and Animal Squat (England, 2019). The political and militant experience of disseminating part of this material in Brazil through the Anarchist Education Laboratory (LEA) is also contextualized. Lastly, the conceptions of children’s literature and child / childhood are discussed, defending a political position of anti-adultcentrism.